Language Aptitude 2019
DOI: 10.4324/9781315122021-11
|View full text |Cite
|
Sign up to set email alerts
|

Declarative and Procedural Memory as Individual Differences in Second Language Aptitude

Abstract: We would like to thank Robert DeKeyser for comments on an earlier version of this chapter, as well as attendees of the 2017 International Round Table Forum on Language Aptitude at the Macao Polytechnic Institute. We also thank members of the Cognition of Second Language Acquisition Laboratory at the University of Illinois at Chicago for helpful comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(92 reference statements)
1
13
0
Order By: Relevance
“…In regard to the former, the present positive findings are in line with previous research that has attested the role of working memory as an important predictor of L2 learning (e.g., Ando et al 1992;Indrarathne and Kormos, 2018;Juff and Harrington, 2011;Linck et al, 2014;Malone, 2018;Yang et al, 2017). Concerning the latter, the results support the theoretical predictions (Ullman, 2015(Ullman, , 2016 that suggest a role for declarative memory in the acquisition of L2 word knowledge (Buffington and Morgan-Short, 2019;Hamrick et al, 2018;Ullman, 2015Ullman, , 2016Ullman and Lovelett, 2018), but contradict earlier labbased research that found no evidence for such a role (Ruiz et al, 2018). However, the association between declarative memory and lexical learning depended on the kind of test used to measure learners' declarative memory abilities.…”
Section: Research Question 1: Do Working Memory and Declarative Memorsupporting
confidence: 92%
“…In regard to the former, the present positive findings are in line with previous research that has attested the role of working memory as an important predictor of L2 learning (e.g., Ando et al 1992;Indrarathne and Kormos, 2018;Juff and Harrington, 2011;Linck et al, 2014;Malone, 2018;Yang et al, 2017). Concerning the latter, the results support the theoretical predictions (Ullman, 2015(Ullman, , 2016 that suggest a role for declarative memory in the acquisition of L2 word knowledge (Buffington and Morgan-Short, 2019;Hamrick et al, 2018;Ullman, 2015Ullman, , 2016Ullman and Lovelett, 2018), but contradict earlier labbased research that found no evidence for such a role (Ruiz et al, 2018). However, the association between declarative memory and lexical learning depended on the kind of test used to measure learners' declarative memory abilities.…”
Section: Research Question 1: Do Working Memory and Declarative Memorsupporting
confidence: 92%
“…Three theoretical perspectives predict a role for procedural memory and knowledge in L2 acquisition: the Skill Acquisition Theory (DeKeyser, 2020), Ullman's Declarative/Procedural Model (Ullman, 2020), and Paradis' Neurolinguistic Theory of Bilingualism (Paradis, 2009). Although there are important differences among these perspectives (Buffington & Morgan-Short, 2019; Morgan-Short & Ullman, submitted), they agree in viewing procedural memory and knowledge as involved in the fluent production and comprehension of grammar in a second language, at least at higher levels of proficiency. Empirical research has begun to examine the association between procedural memory learning ability and L2 grammatical development (Antoniou et al, 2016;Ettlinger et al, 2014;Faretta-Stutenberg & Morgan-Short, 2018;Hamrick, 2015;Morgan-Short et al, 2014;Morgan-Short et al, 2015;Pili-Moss et al, 2020;Suzuki, 2018).…”
Section: Procedural Memory and Its Relation To L2 Acquisitionmentioning
confidence: 99%
“…Given the implicit nature of procedural memory, understanding its role in L2 should be informative to perspectives on implicit language aptitude. Indeed, empirical research that has specifically investigated the role of procedural memory in L2 grammar suggests that individual differences in procedural memory learning ability are associated with L2 development at least at later stages of learning (see Buffington & Morgan-Short, 2019;Hamrick et al, 2018). This body of research has used various assessments of procedural memory learning ability but has yet to establish the reliability and validity of these assessments, which is critical for the internal validity of each study as well as for the robustness of conclusions that can be drawn across studies.…”
mentioning
confidence: 99%
“…It is primarily involved in the processing, storage, and retrieval of information about facts (semantic knowledge) and events (episodic knowledge; Eichenbaum, 2004; Squire, 2004). Learning in this system is posited to be quick, intentional, attention-driven, and predominantly explicit (Buffington and Morgan-Short, 2018; Chun, 2000; Morgan-Short and Ullman, 2012; Ullman and Pullman, 2015; Knowlton et al, 2017). Moreover, it is hypothesized that learning in the declarative memory system can take place after a single exposure (e.g., to a word–meaning association), though this learning is strengthened through additional exposure (Lum et al, 2012; Ullman and Lovelett, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In L2, the declarative memory system is also thought to underlie the learning, storage, and processing of grammar, at least in the initial stages of acquisition (Morgan-Short et al, 2014; Hamrick, 2015). Recent reviews on the topic (e.g., Buffington and Morgan-Short, 2018; Hamrick et al, 2018) as well as our own literature search indicate that no study has yet examined the role of declarative memory and L2 vocabulary acquisition. The prediction below (RQ4) is therefore based on research on child language acquisition and theories of declarative memory as a general-purpose learning system.…”
Section: Introductionmentioning
confidence: 99%